THE EXOTICISM OF THE FILM MARLINA THE MURDERER IN FOUR ACTS AS AN INTRODUCTION TO SUMBA TOURISM - Sabella, Alief Syahda; Fikri, M. Andi (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to examine the role of the film Marlina the Murderer in Four Acts (2017) in promoting Sumba tourism by analyzing how visual elements, dialogue, and cultural representations construct an image of exoticism and authenticity associated with Sumba Island, East Nusa Tenggara. Method: The research employs a qualitative approach using Roland Barthes’ semiotic framework, focusing on three levels of meaning—denotation, connotation, and myth. Data were collected through in-depth scene observation, documentation, and supporting literature on tourism and film studies. Results: The findings reveal that the film highlights distinctive cultural and natural features of Sumba, including Sandalwood horses, the Tanarara savanna hills, the local language, and traditional transportation. These elements not only emphasize cultural identity but also create an imaginative narrative of exoticism that strengthens the destination’s appeal and positions Sumba as a unique cultural tourism site. Novelty: This research contributes to the understanding of film as an indirect yet powerful medium for tourism promotion, offering insights into how cinematic representation can shape destination branding and suggesting a collaborative role for government, tourism stakeholders, and filmmakers in cultural-based tourism development.